Analisis Potensi Lingkungan Familia di Stasi Santo Ignatius Pala Pulau Paroki Hati Santa Perawan Maria Tak Bernoda Putussibau Keuskupan Sintang Sebagai Komunitas Basis Gerejawi (KBG) - Angella Dessy Pebriani; Angga Satya Bhakti; Theresia Yovita Cendana Sari (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
As a communion of believers, the Catholic Church uses a variety of faith-enhancing strategies to uphold the beliefs of its members. One of those efforts is developing a local ecclesial lifestyle calledBasic Ecclesial Community. The Sintang Diocese employs the term “Lingkungan” (English: neighborhood) or